-15x+15=12x

Simple and best practice solution for -15x+15=12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15x+15=12x equation:


Simplifying
-15x + 15 = 12x

Reorder the terms:
15 + -15x = 12x

Solving
15 + -15x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
15 + -15x + -12x = 12x + -12x

Combine like terms: -15x + -12x = -27x
15 + -27x = 12x + -12x

Combine like terms: 12x + -12x = 0
15 + -27x = 0

Add '-15' to each side of the equation.
15 + -15 + -27x = 0 + -15

Combine like terms: 15 + -15 = 0
0 + -27x = 0 + -15
-27x = 0 + -15

Combine like terms: 0 + -15 = -15
-27x = -15

Divide each side by '-27'.
x = 0.5555555556

Simplifying
x = 0.5555555556

See similar equations:

| 4x+4y=432 | | 5a+2b+3a= | | -7b-7(3b+4)= | | (x/4)^20 | | f(x)=Log(4x+12) | | 2-10=x/-7 | | 2a-4b+3b+3a= | | 3a^5-39a^3+108a=0 | | 4a-2x+7a-x= | | 2y=-13(x-5) | | 2x-3y+x-4y= | | 3x-5y-(-3x)= | | 3a+b-(-2b)= | | 4a-5c+3a-c= | | 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t |

Equations solver categories